The Concept of Whole and Integral Islamic Education According to Muhammad Quthb - Albany, Sulistiono Shalladdin; Musthofa, Agus Syafrudin; Fatchurrahman, Achmad Muzaki (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2025)
Education is one of the efforts to develop oneself and build world civilization. One of the efforts of a person to improve the quality of life is through complete and high-quality education. Therefore, a good educational space will have a positive impact on the quality of human resources in a countryThis research aims to explore the urgency of Islamic education from Muhammad Qutb's perspective, which is very important to achieve a complete understanding of Islamic education theory and its development. This type of research is library research (library study), library research seeks to reveal new concepts by reading and recording relevant information, using descriptive analysis methods, namely efforts to collect and compile data, then analyze the data using content analysis, namely examining what is contained in the texts of research data sources. Based on the basic aspects of humans, namely: physical, spiritual and intellectual. Muhammad Qutb stated that humans consist of three integral elements, namely: physical, spiritual and intellectual. Furthermore, he stated that the spirit, mind and body all three form one complete being called human. The development of complete and integral education is realized through a learning approach through example, stories, punishment, events, habits and advice. This approach is a practical step to develop education as a whole and integrally